Gold adorned pages: Exploring the distinguished Gold Paint of Assam - Boruah, Porishmita (International Journal of Psychosocial Rehabilitation, 2020)
The beautiful art of gilding manuscript is one of the distinct features of the paintings in Assam. This process is popularly known as ‘Kham’ amongst the Theravada Buddhists of Assam and in Assamese, it is called Sonar-pani-charowa. Painting tradition of Assam is mostly found in the form of books illustration or manuscript painting. A variety of color palettes were used to make the illustrations lively. Yellow and green were most prominent colors in illustrations, except that Tai-Ahom School of painting used blue, red, black and gold. Use of gold in the color palette is one of the unique features of Tai-Ahom School. Gold was liquidated in a specific process to use as a color. It has also been used rarely, sometimes to indicate the heart of Buddha. In order to make the study accurate, emphasis is laid on both primary and secondary sources. Archival records served the purpose of primary source. Books, journals and articles on this content also helped a lot in framing the current investigation. The Tai-Ahom style of painting cherished the unique process of gold painting. Except for the Tai-Ahom School, nowhere in Assam the use of gold paint and gold leaf folios for writing Manuscripts can be found. The Cultural connection between Upper Burma and Upper Assam facilitates the growth of gold paint in Assam. In Assam, gold in dust form is used in the technique of preparing Kham. Later on, due to lack of extensive practice, propagation of Hinduism amongst the Tai Ahom people of the valley, gilding of manuscript gradually disappeared.